Characterization of Histone Deacetylase Expression Within In Vitro and In Vivo Bladder Cancer Model Systems - Buckwalter, Jenna M. (Int J Mol Sci, 2019)
Epigenetic aberrations are prominent in bladder cancer (BC) and contribute to disease pathogenesis. We characterized histone deacetylase (HDAC) expression, a family of deacetylation enzymes, in both in vitro and in vivo BC model systems and analyzed expression data from The Cancer Genome Atlas (TCGA). Quantitative real-time polymerase chain reaction (qRT-PCR) and western blotting analysis was used to determine the expression status of Class I and II HDACs in ten human BC cell lines, while qRT-PCR was used to determine HDAC expression in 24 human tumor specimens. The TCGA cohort consists of 408 muscle invasive BC (MIBC) clinical samples and analysis of this data set identified expression of HDAC4 and -9 as being associated with basal–squamous disease. These findings agree with qRT-PCR results identifying increased expression of HDAC4, -7, and -9 in basal BC cell lines (p < 0.05; Kruskal–Wallis test) and in clinical specimens with invasive bladder cancer (not statistically significant). We also observed increased expression in Hdac4, -7, and -9 in commonly used BC mouse models. Here, we identify suitable preclinical model systems for the study of HDACs, and show increased expression of Class IIa HDACs, specifically HDAC4 and HDAC9, in basal BC cell lines and in invasive clinical specimens. These results suggest this class of HDACs may be best suited for targeted inhibition in patients with basal BC.